2018
DOI: 10.1063/1.5036710
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap and band edge positions in compositionally graded ZnCdO

Abstract: Introducing Cd into ZnO allows for bandgap engineering, potentially with particularly interesting properties to observe in compositionally graded samples. In this work, compositionally graded Zn 1-x Cd x O samples with 0 x < 0.16 were made using metal organic vapour phase epitaxy. The chemical composition was studied using scanning transmission electron microscopy, while the band structure of the samples was investigated using a combination of cathodoluminescence spectroscopy and X-ray photoelectron spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For example, for a WZ alloy with x = 0.4, the VBM would be higher than that of ZnO by ∼1 eV. 11 On the other hand, Jensen et al suggested that the downward shift of the conduction band minimum (CBM) in the alloy with increasing x accounts for the bandgap narrowing, 37 implying that the formation of native donor defects becomes easier for CdZnO thin films with high Cd contents. While the downward shift of CBM and upward shift of VBM could occur simultaneously as x increases, the larger reduction in n for alloys with low x suggests that the reduction in the formation energy of native donors has a stronger impact on electrical properties than native acceptors.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…For example, for a WZ alloy with x = 0.4, the VBM would be higher than that of ZnO by ∼1 eV. 11 On the other hand, Jensen et al suggested that the downward shift of the conduction band minimum (CBM) in the alloy with increasing x accounts for the bandgap narrowing, 37 implying that the formation of native donor defects becomes easier for CdZnO thin films with high Cd contents. While the downward shift of CBM and upward shift of VBM could occur simultaneously as x increases, the larger reduction in n for alloys with low x suggests that the reduction in the formation energy of native donors has a stronger impact on electrical properties than native acceptors.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…Doping ZnO with different elements, including transition metals (TM) such as Mn, Cd, Ni, and Co, has been shown effective in changing the absorption edge of the ZnO-based materials. [12][13][14] This phenomenon is related to the effect of energy band bending resulted from the formation of TM-related impurity clusters in the ZnO structure. [15][16][17] This shows the potential for the growth of doped ZnO thin films with a lower optical bandgap energy, which can be used for various photoabsorbing or sensing applications in the longer wavelength range.…”
mentioning
confidence: 99%